2022
DOI: 10.1090/proc/15807
|View full text |Cite
|
Sign up to set email alerts
|

Singularity of random symmetric matrices revisited

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(45 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…It was noted in [ 8 ] that given the techniques in [ 3, 8 ], Theorem 1·1 (with the weaker probability bound ) can be deduced from the following universality statement: the probability that is invertible over , for , is essentially the same as for an symmetric matrix whose entries on and above the diagonal are sampled from the uniform distribution on . Despite the intensive efforts to study the singularity probability of symmetric Rademacher matrices ([ 4, 6, 7, 10, 14, 20, 24 ] and especially the recent breakthrough [ 5 ] which confirms the long-standing conjecture that the singularity probability of symmetric Rademacher matrices is exponentially small), a result of this precision has remained elusive. While for , such a result is known due to work of Maples [ 18 ], the bound on p is too restrictive to imply Theorem 1·1 (even with the weaker probability ).…”
Section: Introductionmentioning
confidence: 99%
“…It was noted in [ 8 ] that given the techniques in [ 3, 8 ], Theorem 1·1 (with the weaker probability bound ) can be deduced from the following universality statement: the probability that is invertible over , for , is essentially the same as for an symmetric matrix whose entries on and above the diagonal are sampled from the uniform distribution on . Despite the intensive efforts to study the singularity probability of symmetric Rademacher matrices ([ 4, 6, 7, 10, 14, 20, 24 ] and especially the recent breakthrough [ 5 ] which confirms the long-standing conjecture that the singularity probability of symmetric Rademacher matrices is exponentially small), a result of this precision has remained elusive. While for , such a result is known due to work of Maples [ 18 ], the bound on p is too restrictive to imply Theorem 1·1 (even with the weaker probability ).…”
Section: Introductionmentioning
confidence: 99%
“…We now turn to discuss our second approximate negative dependence result, which deals with the intersection of two different small ball events. This was originally proved in our paper [4], but is put to a different use here. This result tells us that the events…”
Section: Approximate Negative Correlationmentioning
confidence: 72%
“…He went on to conjecture that 𝜀 should replace 𝜀 1/8−𝜀 as the correct order of magnitude, and that 𝑒 −𝑐𝑛 should replace 𝑒 −𝑛 𝑐 . After Vershynin, a series of works [3,5,16,17,19] made progress on singularity probability (i.e., the 𝜀 = 0 case of Vershynin's conjecture), and we, in [4], ultimately showed that the singularity probability is exponentially small, when 𝐴 𝑖, 𝑗 is uniform in {−1, 1}:…”
Section: History Of the Least Singular Value Problemmentioning
confidence: 99%
See 2 more Smart Citations